Dutch Public health Foresight study 2018/20. (30th September 2020) - Hilderink, H
Abstract: The four-year Public Health Foresight Study (VTV) provides insight into the most important societal challenges for public health and health care in the Netherlands. The seventh edition of the Dutch Public Health Foresight study was published in 2018, with an update in 2020. In this update a business-as-usual or Trend Scenario was developed using 2018 as a base year. In the trend scenario demographic and epidemiological projections have been used to depict the future trends regarding ageing, health, disease, health behaviors, health expenditures and health inequalities. Next, these trends are used to identify the most important future challenges and opportunities for public health. In the 2020 update, special attentions is given to climate change and the local living environment and their impacts and interaction with public health outcomes. Trends in lifestyle-related lifestyle show both positive (smoking prevalence) and negative (overweight prevalence) future developments. Dementia will be the leading cause of mortality and disease burden in 2040 by far. Health care expenditures will double by 2040, with cancers showing the most rapid growth of all disease groups. The insights of this study are directly used as input for the National Health Policy Memorandum and for the National Prevention Accord.